Efficient total synthesis of decarestrictine D - Guptali, Priti; Kumar, Pradeep (European Journal of Organic Chemistry, 2008)
An efficient total synthesis of decarestrictine D has been achieved using cross-metathesis or ring-closing metathesis and Yamaguchi macrolactonization as key steps. The stereogenic centres were generated by means of hydrolytic kinetic resolution (HKR) and Sharpless asymmetric dihydroxylation (AD).
Keywords: Cross metathesis; Hydrolytic kinetic resolution; Macrolides; Ring-closing metathesis; sharpless asymmetric dihydroxylation